PERSPEKTIF GURU TENTANG SCREEN TIME DAN PERKEMBANGAN BAHASA ANAK USIA DINI - Anisa Triyani; Vava Iman Agus Faisal (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This research aims to describe language development in children with excessive screen time duration through the perspective of teachers at Aisyiyah Kindergarten 02 Pasurenan. The method used is qualitative descriptive with data collection techniques through structured interviews with class teachers and direct observation of the learning process. Research results show significant differences in communication patterns; children with high screen time intensity tend to be more silent, insulative, and only respond to one word. There was also an ecolalia phenomenon in which children imitate foreign terms from videos without understanding their meaning, as well as a decrease in focus when interacting directly. This study concluded that collaboration between teachers and parents in limiting screen duration as well as increasing interactive activities such as role-playing is essential to optimizing children's expressive and receptive language abilities.